2022
DOI: 10.1172/jci157399
|View full text |Cite
|
Sign up to set email alerts
|

Targeting FAPα-expressing hepatic stellate cells overcomes resistance to antiangiogenics in colorectal cancer liver metastasis models

Abstract: Vessel co-option has been demonstrated to mediate colorectal cancer liver metastasis (CRCLM) resistance to anti-angiogenic therapy. The current mechanisms underlying vessel co-option have mainly focused on the "hijacker" tumor cells, whereas the function of the "hijackee" sinusoidal blood vessels has not been explored. Here, we found that the occurrence of vessel co-option in bevacizumab-resistant CRCLM xenografts was associated with increased expression of fibroblast activation protein alpha (FAPα) in the co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 72 publications
1
19
0
Order By: Relevance
“…In this research, the program SCENIC 23 was employed to identify TFs and their corresponding targets that exhibit elevated levels of activity in a specific subtype of CAFs compared to other subtypes. It was revealed that the distribution of EGR1 was present in all clusters, suggesting its potential role in mediating RNA in fibroblasts to promote cell cycle progression and carcinogenesis in different malignancies 31,32 . Our study revealed an enrichment of CREB5, RUNX3, and HIVEP2 in iCAFs, which were previously been implicated in promoting invasiveness and metastasis in colorectal cancer and head and neck malignancies 33,34 .…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…In this research, the program SCENIC 23 was employed to identify TFs and their corresponding targets that exhibit elevated levels of activity in a specific subtype of CAFs compared to other subtypes. It was revealed that the distribution of EGR1 was present in all clusters, suggesting its potential role in mediating RNA in fibroblasts to promote cell cycle progression and carcinogenesis in different malignancies 31,32 . Our study revealed an enrichment of CREB5, RUNX3, and HIVEP2 in iCAFs, which were previously been implicated in promoting invasiveness and metastasis in colorectal cancer and head and neck malignancies 33,34 .…”
Section: Resultssupporting
confidence: 52%
“…It was revealed that the distribution of EGR1 was present in all clusters, suggesting its potential role in mediating RNA in fibroblasts to promote cell cycle progression and carcinogenesis in different malignancies. 31,32 Our study revealed an enrichment of CREB5, RUNX3, and HIVEP2 in iCAFs, which were previously been implicated in promoting invasiveness and metastasis in colorectal cancer and head and neck malignancies. 33,34 The expression level of TFs MYF6, MYF5, MYOD1, and MYOG were found to be significantly elevated in myCAFs, with their respective target genes serving as biomarkers for myofibroblast.…”
Section: Cafs Subtype-specific Tfs and Gene Regulatory Networkmentioning
confidence: 58%
“…37,87 Interactions between cancer cells and HSCs maintain the activation phenotype of HSCs in a positive feedback manner, forming a microenvironment that promotes liver metastasis. 88,89 Vasodilator-stimulated phosphoprotein (VASP) is a regulator of the actin cytoskeleton. Tu et al found that CRC cells induced VASP upregulation in HSCs, sensitizing HSCs to TGF-β.…”
Section: Hscsmentioning
confidence: 99%
“…CAFs consist of mesenchymal fibroblasts and α‐smooth muscle actin (α‐SMA)‐positive myofibroblasts, which are major components of the metastatic CRC tumor microenvironment 37,87 . Interactions between cancer cells and HSCs maintain the activation phenotype of HSCs in a positive feedback manner, forming a microenvironment that promotes liver metastasis 88,89 . Vasodilator‐stimulated phosphoprotein (VASP) is a regulator of the actin cytoskeleton.…”
Section: Nonparenchymal Cells Of the Livermentioning
confidence: 99%
“…Overexpression of FAP in tumors has been shown to promote tumor growth, angiogenesis [ 11 ], and metastasis [ 12 ]. Silencing FAP has been shown to induce tumor cell apoptosis [ 13 ], indicating its important role in cancer cells survival. Moreover, a high level of FAP expression in the stroma is associated with aggressive disease progression and recurrence in colorectal cancer [ 14 ].…”
Section: Introductionmentioning
confidence: 99%